1977
DOI: 10.1159/000127963
|View full text |Cite
|
Sign up to set email alerts
|

Intraportal and Intrasplenic Autotransplantation of Pancreatic Islets in the Dog

Abstract: Autotransplantation of pancreatic microfragments into the liver or the spleen of totally pancreatectomized dogs is described. Both modes of transplantation resulted in restoration of normal fasting blood glucose levels. A delayed response to high glucose loads was however observed in both groups. Serum amylase levels indicated a rapid decline of exocrine activity. On the basis of postoperative levels of GOT and GPT in the serum of the dogs with intraportal transplants, permanent proteolytic or ischemic damage … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
16
0

Year Published

1981
1981
2018
2018

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 40 publications
(16 citation statements)
references
References 4 publications
(4 reference statements)
0
16
0
Order By: Relevance
“…Numerous studies have been conducted using such preparations of islets in dogs after either direct injections of the splenic pulp (2, [4][5][6][7][8] or after retrograde reflux into splenic venous tributaries (9,10). Although there have been a few citations (7)(8)(9) of long-term functional survival of islet autografts prepared by these techniques, continuing islet autograft function has not yet been studied in detail.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Numerous studies have been conducted using such preparations of islets in dogs after either direct injections of the splenic pulp (2, [4][5][6][7][8] or after retrograde reflux into splenic venous tributaries (9,10). Although there have been a few citations (7)(8)(9) of long-term functional survival of islet autografts prepared by these techniques, continuing islet autograft function has not yet been studied in detail.…”
Section: Introductionmentioning
confidence: 99%
“…Although there have been a few citations (7)(8)(9) of long-term functional survival of islet autografts prepared by these techniques, continuing islet autograft function has not yet been studied in detail. Also, islet preparations by these techniques have not usually been transplanted into the portal venous system due to the threat of inducing portal hypertension or other complications associated with exocrine secretions (1 [1][2][3][4][5][6][7][8][9][10][11][12][13].…”
Section: Introductionmentioning
confidence: 99%
“…A number of different techniques of splenic islet autotransplantation have been described including direct intrasplenic injection [11, 101, 102], arterial [11]and retrograde venous infusion [40, 103, 104, 105, 106]. In comparison, the latter method is the most commonly preferred [90, 105].…”
Section: Surgical Considerations In Pancreatectomy and Autologous Islmentioning
confidence: 99%
“…Several investigators have since used the model of intrasplenic transplantation of dispersed pancreatic tissue in dogs to study a variety of problems, including preservation [179,180], systemic versus portal venous drainage [181], the effect of endogenous pancreatic tryptic activity on the islet preparation [178] and the metabolic responses after transplantation [102,177]. Mehigan et al [107] found that the success rate was lower with transplantation of tissue prepared from dogs with chronic pancreatitis induced by duct ligation even though the insulin reserve of the pancreas before dispersion was nearly normal.…”
Section: Dispersed Adult Pancreas Without Islet Purificationmentioning
confidence: 99%
“…Diabetes has also been treated by infusion of collagenase dispersed pancreatic tissue into the portal vein of pancreatectomized dogs [177,183]. Serum liver enzyme levels are transiently elevated.…”
Section: Dispersed Adult Pancreas Without Islet Purificationmentioning
confidence: 99%